KAMPANYE PENANGKALAN HOAX MELALUI APLIKASI GAWAI - CALVIN PALTI JUNJUNGAN SINAGA; JESSICA YONATIA (Serat Rupa: Journal of Design, 2018)
The hoax is known as a familiar term for netizen nowadays, which its meaning is a public lie that made and spread irresponsibly through the internet. The hoax has become something that troubling yet misleading the netizen since they majority netizen receives news through the internet without noticing the credibility of the authors. The worst impact of hoax would be the split of the nation’s unity. Hoax itself is not something that hard to be opposed to if the netizen has media literacy knowledge, which is having a critical attitude to the news that spread through the internet. Therefore, this social campaign about educating media literacy was created towards netizen in the big cities of Indonesia. The design method used in this campaign is using a visual compilation of photography and pop art vector, with gadget application as the main media, and the supporting medias such as a serial poster in social media, mini event, website, and gimmick. The main goal of this campaign is to educate netizen about media literacy and the next expected goal is the appearance of critical and selective attitude towards news that spread on the internet.